THE CHALLENGE OF HIV/AIDS TO CHRISTIAN THEOLOGY - Ndungane, Njongonkulu (Scriptura, 2005)
In this article Archbishop Ndungane reflects on various aspects related to the challenge that HIV/Aids poses to the church in South Africa and to Christian theology. He draws on biblical motifs to address a wide range of issues such as stigma, gender, youth, children, suffering, healing death, funerals and the availability of resources to address the pandemic.